To solve the quadratic equation \( x^2 - 22x + 1 = 15 \) by completing the square, we first rewrite the equation in standard form:
-
Subtract 15 from both sides: \[ x^2 - 22x + 1 - 15 = 0 \implies x^2 - 22x - 14 = 0 \]
-
Move the constant term to the right: \[ x^2 - 22x = 14 \]
-
To complete the square, take half of the coefficient of \( x \) (which is \(-22\)), square it, and add it to both sides. Half of \(-22\) is \(-11\), and squaring it gives \(121\): \[ x^2 - 22x + 121 = 14 + 121 \] \[ x^2 - 22x + 121 = 135 \]
-
Now, the left side can be factored as: \[ (x - 11)^2 = 135 \]
-
Taking the square root of both sides gives: \[ x - 11 = \pm \sqrt{135} \]
-
Finally, solve for \( x \): \[ x = 11 \pm \sqrt{135} \]
Now, simplify \(\sqrt{135}\): \[ \sqrt{135} = \sqrt{9 \times 15} = 3\sqrt{15} \]
Thus, the solutions can be expressed as: \[ x = 11 + 3\sqrt{15}, \quad x = 11 - 3\sqrt{15} \]
Based on the available responses, the correct answer is: x = 11 + 3√15, 11 - 3√15.